Raising Environmental Awareness Among Elementary School Students through Eco-Enzyme Training at SDN 33 Padang - Awalina, Rahmi; Hasbullah, Hasbullah; Koja, Reni; Wellyalina, Wellyalina; Puari, Aninda Tifani; Novelina, Novelina; Efrina, Efrina (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2025)
This community service activity was carried out by the Community Service Team of the Faculty of Agricultural Technology, Andalas University, in collaboration with SD Negeri 33 Rawang Barat, Padang City. The activity took place in the school meeting room and aimed to educate elementary school teachers and students on the utilization of organic waste through the process of making, harvesting, and applying eco-enzymes. The program included socialization, education about eco-enzymes, hands-on training, and demonstrations of their production and use. This initiative provided various benefits, particularly in environmental education, character building, and practical skills development. Students were introduced to the types of organic waste and their impact on the environment. The activities are carried out in several stages: providing educational materials, practical sessions on the production and harvesting of eco-enzymes, and interactive discussions. The results of this knowledge transfer are expected to increase the role of schools in shaping students with ecological awareness and encouraging responsible behavior towards waste management. This early intervention aims to instill sustainable environmental awareness and empower students as agents of change in environmentally friendly waste management practices.